Rise Velocity and Drag Coefficient of Collapsing Two-Phase Bubble Condensing in an Immiscible Liquid - A. Abdul-Majeed, Basma (Iraqi Journal of Chemical and Petroleum Engineering, 2007)
Collapse of the vapor bubble condensing in an immiscible is investigated for n-pentane and n-hexane vapors condensing in cold water and n-pentane in two different compositions of glycerin- water mixture. The rise velocity and the drag coefficient of the two-phase bubble are measured.